2012
DOI: 10.3113/fai.2012.0379
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma Treatment for Chronic Achilles Tendinosis

Abstract: Platelet-rich plasma was used effectively to treat chronic recalcitrant cases of Achilles tendinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 52 publications
(90 reference statements)
2
67
0
1
Order By: Relevance
“…Owens et al 47 reported modest improvement in functional outcome in 10 patients who had received PRP injection for mid substance Achilles tendinopathy. Monto et al 48 reported clinical success in 28 out of 30 patients with recalcitrant Achilles tendinosis. The improvement noted was in the AOFAS score and the MR architecture of the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Owens et al 47 reported modest improvement in functional outcome in 10 patients who had received PRP injection for mid substance Achilles tendinopathy. Monto et al 48 reported clinical success in 28 out of 30 patients with recalcitrant Achilles tendinosis. The improvement noted was in the AOFAS score and the MR architecture of the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Over eight clinical human trials, the vast majority of patients suffering from chronic, recalcitrant tendinosis saw significant and substantial reductions in pain [88][89][90][91][92][93][94][95] and increases in joint function [72,88,90,[92][93][94][95] when treated with PRP without supplemental procedures. These patients had experienced symptoms of tendonosis for at least 3 months and had not responded to nonsurgical interventions [88][89][90][92][93][94][95]. Raymond Monto treated 30 patients experiencing severe, persistent Achilles tendinopathy with a single 4 mL injection of PRP [90].…”
Section: Prp For Chronic Tendinopathiesmentioning
confidence: 99%
“…These patients had experienced symptoms of tendonosis for at least 3 months and had not responded to nonsurgical interventions [88][89][90][92][93][94][95]. Raymond Monto treated 30 patients experiencing severe, persistent Achilles tendinopathy with a single 4 mL injection of PRP [90]. After 2 years, mean pain scores had improved dramatically.…”
Section: Prp For Chronic Tendinopathiesmentioning
confidence: 99%
“…Several under powered studies have reported favorable results by the use of PRP for different tendon injuries [33][34][35][36][37][38][39][40] . Several well structured clinical randomized controlled trials [41][42][43][44][45][46][47][48][49][50][51][52][53] report no significant differences when PRP was compared to controls for the treatment of tendinopathy (elbow, achilles, rotator cuff, plantar fascia), rotator cuff and achilles tendon ruptures.…”
Section: Human Studiesmentioning
confidence: 99%